Edmund Russell, Evolutionary History: Uniting History and Biology to Understand Life on Earth (Cambridge: Cambridge University Press, 2011), xviii + 216 pp. ISBN: 9-780-52174-509-3. £18.99 pbk. (15th June 2017) - Brunelli, Andrea
Abstract : Edmund Russell, Evolutionary History: Uniting History and Biology to Understand Life on Earth (Cambridge: Cambridge University Press, 2011), xviii + 216 pp. ISBN: 9-780-52174-509-3. £18.99 pbk.